FRG and GDR in the third world - Dietrich Kebschull (Intereconomics, 1971)
Together with its “Report on the State of the Nation 1972” the Government of the Federal Republic of Germany presented an extensive collection of studies. Drawn up by 50 experts, the report on the development in the two German states should, according to Willy Brandt, contribute to facilitate political judgement and to sobering political discussion. In our last edition we published a summary of the chapter on the State of the Nation's External Economy. This paper is a summary of the two German states' development aid. The author, in cooperation with Hans-Ludwig Dornbusch and Dieter W. Vogelsang, participated in the composition of this chapter.
Keywords: 330; Germany